PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 105 PEKANBARU - Harni Dasrianti Dasrianti; Hendri Marhadi Marhadi; ZariuL Antosa Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research carried out base on the lowly of the result of social subject in grade 5th SDN 105 Pekanbaru which is about 57,36 within minimal completeness criterion stated is 70. Among 38 student, there was only 13 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on social of the five graders in SDn 105 Pekanbaru with the application of contextual teaching and learning model. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of contextual teaching and learning model it was abtained student’s outcomes in UH I within average 68,25 (improved from basic score 18,98%). The average score form UH II was 74,85 (improved 30,49%). Teachers activities results in the first meeting of the first cycle was 65% (good category), and then 70% (good category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 85% (very good category) and then 90% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 50% (fair category), 70% (good category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was 80% (good category), 85% (very good category) for the second meeting in cycle II. Based on the result it can be concluded that implementation of contextual teaching and learning model can social in five graders at SDN 105 Pekanbaru Keywords : Contextual Teaching and Learning, Students Achievement the Result Of Social Studies.